2014
DOI: 10.3855/jidc.3989
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial and molecular analysis of Salmonella serovar Livingstone strains isolated from humans in Tunisia and Belgium

Abstract: Introduction: Salmonella Livingstone is one of the most common serotypes responsible for nosocomial outbreaks in Tunisia. In this study, 42 isolates of Salmonella Livingstone were analyzed. Most of these were isolated from humans (31 strains from Tunisia and 9 strains from Belgium) and 2 isolates came from food products (beef and pork). Methodology: All strains were characterized by antibiogram, multilocus sequence typing (MLST), and virulotyping. This last technique was carried out by simple PCR of five chrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 48 publications
(72 reference statements)
1
6
1
Order By: Relevance
“…- The spv ( Salmonella plasmid virulence) operon was found to be associated with Salmonella survival and growth in macrophages by Rychlik et al (2006), and appeared to be only present in serovars Typhimurium and Enteritidis in our study. Huehn et al (2010), Guedda et al (2014), and Hoffmann et al (2014) all showed comparable results with the spv operon being present in Typhimurium and Enteritidis, but absent in other serovars under investigation.…”
Section: Discussionsupporting
confidence: 57%
“…- The spv ( Salmonella plasmid virulence) operon was found to be associated with Salmonella survival and growth in macrophages by Rychlik et al (2006), and appeared to be only present in serovars Typhimurium and Enteritidis in our study. Huehn et al (2010), Guedda et al (2014), and Hoffmann et al (2014) all showed comparable results with the spv operon being present in Typhimurium and Enteritidis, but absent in other serovars under investigation.…”
Section: Discussionsupporting
confidence: 57%
“…Salmonella Livingstone strains were assigned to ST543. This result was only reported in Salmonella Livingstone in Belgium study (http://mlst.ucc.ie/ mlst/dbs/Senterica) and recently in Tunisia (10).…”
Section: Discussionmentioning
confidence: 80%
“…In Sfax Hospital, Salmonella Livingstone is responsible for nosocomial outbreaks between 2000 and 2003 . This serovar has recently been reported as responsible of nosocomial outbreak occurred in the neonatology ward maternity department in Sousse hospital (central east of Tunisia) .…”
mentioning
confidence: 99%
“…Genomic DNA was extracted according to Guedda et al [ 17 ] with slight modification. One to five bacterial colonies were suspended in 100 ml of nuclease free water and suspension was heated at 100 °C for 10 min.…”
Section: Main Textmentioning
confidence: 99%